A comparative study on the accumulation of toxic heavy metals in fish of the Oman Sea: effects of fish size, spatial distribution and trophic level. (2nd January 2023) - Javanshir Khoei, Arash
Abstract: This study was conducted to evaluate heavy metal (HMT) accumulation in some commercially pelagic ( Scomberoides commersonnianus, Rastrelliger kanagurta, Saurida tumbil ) and demersal fish ( Parastromateus niger, Alepes melanoptera, Nemipterus japonicus, Alepes melanoptera ) of Oman Sea. Fish samples were collected by trawl from inshore area of four stations along Chabahar bay. The heavy metal (Ni, Cr, Hg, Cd, Pb) concentrations in the muscle tissue of the fishes were assayed. In addition, the relationships between the level of heavy metal accumulation in fish tissue and fish size were studied. The demersal species accumulated more heavy metals compared to pelagic fishes ( p  < 0.01). Both in pelagic and demersal fishes, the rate of metal accumulations was different depending on fish species. In addition, the trophic level affected tissue muscular metal concentrations. Both in pelagic and demersal fishes, the carnivorous and euryphagous species accumulated more metals compared to phytoplankton and herbivorous fishes ( p  < 0.01). In most cases, negative relationships were observed between fish size (length and weight) and the metal accumulations ( p  < 0.01). However, some positive correlations were also observed in Hg, Pb and Cd concentrations with size in Psettodes erumei and Parastromateus niger ( p  < 0.01). In conclusion, the different patter of metals accumulations may be attributed to the differences in feeding behavior, metabolic activity and habitat. In this study, except Cd and Cr, the concentrations of all heavy metals were in the safe range and were below the hazardous limits recommended by the EC (2001) and USFDA.